(untitled) (The Research of Medical Science Review, 2025)
Background: Prominent biomarker Ki-67 reflects breast cancer's tumor proliferation. Its relationship with histological grade, menopausal status and hormone receptor status offers important new perspectives on tumor biology that help to guide therapeutic decisions and prognosis. Aims: This study sought to assess, in breast cancer patients presenting at Combined Military Hospital, Rawalpindi, Ki-67 levels, estrogen receptor (ER), progesterone receptor (PR), menopausal state and histological grade. Methods: 180 histologically confirmed breast cancer patients participated in this cross-sectional observational research from October 2024 to March 2025. ER, PR, and Ki-67 expression were ascertained by immunohistochemical labeling. High proliferative tumors were those with ≥20% Ki-67-positive cells. Including multivariate regression, statistical analysis evaluated relationships with p-values <0.05 regarded as significant. Results: Compared to ER-positive (23.4 ± 8.7) and PR-positive tumors (22.1 ± 7.9), mean Ki-67 levels were considerably higher in ER-negative (45.6 ± 12.3) and PR-negative tumors (44.3 ± 10.8) (p<0.01). With the p=0.03, premenopausal patients had greater Ki-67 levels (38.7 ± 9.8) than post-menopausal individuals (34.6 ± 8.4). Following Grade 2 (27.8 ± 8.1) and Grade 1 (12.3 ± 5.6), Grade 3 tumors exhibited the highest Ki-67 values (49.5 ± 11.2) (p<0.01). Strong predictors of elevated Ki-67 levels (p<0.01) were found by multivariate analysis as ER negativity (OR: 2.8), PR negativity (OR: 2.5), and tumor size >3 cm (OR: 2.1). Conclusion: Ki-67 highlighted its importance in prognostic stratification since it is much linked with hormone receptor status, menopausal status and histological grade. These results confirmed how Ki-67 is included into standard breast cancer tests to maximize individualized treatment plans.